(untitled) (TEL Tempo, Espaço e Linguagem, 2024)
This article promotes an analysis of the significant contributions of Dona Ivone Lara, a black woman who played crucial roles in the health sector, intertwining her trajectory with the rich history of samba in Brazil. Working as a nurse, social worker and specialist in occupational therapy from the 1940s onwards, Dona Ivone Lara innovated care practices for people with mental disorders, incorporating music as therapy and actively involving the family and the community in deinstitutionalization processes. The research focuses on the analysis of the song Sorriso Negro, by Adilson Barbado and Jorge Portela, which became a celebration of blackness, inseparable from the figure of Dona Ivone Lara. The study reveals the intersection between its role in health and its influence on the music scene, highlighting its importance in the history of samba and black female resistance.